Whole genome analysis and in vivo safety assessment of probiotic candidate Lactobacillus acidophilus L177 - Yunjiang Liu; Haohong Zheng; Jiali Wang; Jialiang Xin; Ruihu Wu; Jingyi Zhang; Zhijun Zhong; Haifeng Liu; Yixin Huang; Hualin Fu; Ziyao Zhou; Guangneng Peng (BMC Microbiology)
Abstract Probiotics, particularly strains of lactic acid bacteria (LAB), are recognized for their beneficial effects on gut health. Lactobacillus acidophilus L177, a promising probiotic strain isolated from canine feces, was evaluated for safety and probiotic properties through whole genome sequencing and a 28-day subacute oral toxicity study in C57BL/6 mice. The toxicity study involved daily administration of L177 at doses of 108, 109, and 1010 CFU/mL, with continuous monitoring of general health, behavioral changes, and physiological parameters. Body weight, food and water intake, hematological and biochemical indices, organ weights, and histopathology were assessed. No significant adverse effects were observed, and proinflammatory cytokines (TNF-α, IL-6, IL-1β) remained undetectable in serum, indicating an absence of inflammatory response. Statistical analysis confirmed no significant differences in key health markers between treated and control groups (p > 0.05). Whole genome sequencing revealed a single chromosome of approximately 1,972,211 base pairs (GC content: 35.02%) with 1 CRISPR sequence and 1,955 genes. Functional annotation highlighted genes associated with metabolism, information processing, and cellular functions. Antibiotic Resistance Gene analysis identified one AMR gene (lnu(C)), but phenotypic tests confirmed L177 is sensitive to clindamycin and lincomycin. Sixty-seven virulence-associated genes were detected, mainly related to structure, metabolism, and regulation. These findings support the safety and probiotic potential of L. acidophilus L177 for potential applications in both animal and human health.